1973
DOI: 10.1136/thx.28.4.424
|View full text |Cite
|
Sign up to set email alerts
|

Cystic intrathoracic derivatives of the foregut and their complications

Abstract: It is suggested that these lesions should be classified into three main categories based on embryology-bronchogenic cyst (resulting from a defect of lung budding), intramural oesophageal cyst (true duplication), and enteric cyst (resulting from the split notochord syndrome). A series of 41 patients is reported. Seven of our patients suffered complications, and in two cases these nearly resulted in the death of the patient. These complications are described and their serious import is used to emphasize the desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
47
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(48 citation statements)
references
References 8 publications
1
47
0
Order By: Relevance
“…MATZINGER et al [21] reported a case of intrapulmonary bronchogenic cyst in a 16 year old girl presenting with pneumothorax. Other reported complications are pleural effusion [22,23], arrhythmias [24], stenosis of the pulmonary artery [25], unilateral ventilation-perfusion defect [26], pericardial and cardiac tamponade [27], carcinomatous [28] or sarcomatous transformation [29], and giant tension bronchogenic cyst [30]. Intrapulmonary bronchogenic cysts generally present as one of three different patterns on the chest radiograph.…”
Section: Discussionmentioning
confidence: 99%
“…MATZINGER et al [21] reported a case of intrapulmonary bronchogenic cyst in a 16 year old girl presenting with pneumothorax. Other reported complications are pleural effusion [22,23], arrhythmias [24], stenosis of the pulmonary artery [25], unilateral ventilation-perfusion defect [26], pericardial and cardiac tamponade [27], carcinomatous [28] or sarcomatous transformation [29], and giant tension bronchogenic cyst [30]. Intrapulmonary bronchogenic cysts generally present as one of three different patterns on the chest radiograph.…”
Section: Discussionmentioning
confidence: 99%
“…Kirwan et al (5) reported 41 patients with intrathoracic foregut cysts and classified them into three types: bronchogenic, esophageal, and enteric cysts. Bronchogenic cysts occur from extra lung buds, which develop from the primitive foregut.…”
Section: Discussionmentioning
confidence: 99%
“…Enteric cysts are often associated with vertebral anomalies and usually located in the posterior mediastinum with attachment to the dorsal vertebra, and have no connection with the esophagus. These cysts are lined by either gastric mucosa with parietal and chief cells; duodenal, small intestinal, or large intestinal mucosae; or squamous or ciliated columnar epithelium (5).…”
Section: Discussionmentioning
confidence: 99%
“…(9) Unlike cystic duplications, tubular duplications usually communicate with the normal oesophagus. The earliest known description of tubular duplication was made by Kirwan et al, (10) and the second patient was reported by Kathe in 1907. (11) Malignancies in patients with partial duplication have also been reported earlier.…”
Section: Discussionmentioning
confidence: 99%